Most Common Factors Causing Cost Overrun with its Mitigation Measure for Pakistan Construction Industry - Sohu, Samiullah; Ansari, Abdul Aziz; Ahmed Jhatial, Ashfaque (International Journal of Sustainable Construction Engineering and Technology, 2020)
Cost overrun is known as the leading challenge for stakeholders of the construction sector. Like most countries, Pakistan also facing this challenge for the last few decades. Literature review was conducted and managed to identify 34 factors which contributed to cost overrun in the construction industry. These factors were used as the main content in designing the questionnaire. Respondents were required to rate these factors based on 4-ponits Likert scale on the degree of commonly occurred. Survey was carried out involved 130 stakeholders of the construction sector to determine main factors of the overrun. Data was collected, analysed statistically using the average index method and found 10 most commonly occurred of cost overrun factors for Pakistan construction industry are financial crisis faced by the client; mistakes in making proper estimation; faults in drawing; delay in getting approval from the client; poor planning by client; incompetency of contractor; poor supervision of the consultant; delay in payment to the contractor; communication gap between parties and natural disaster. These factors were further explained together with its mitigation measure. The findings of this study can help to Pakistani construction community in controlling the cost overrun for their construction projects.